2014
DOI: 10.1177/1352458514560926
|View full text |Cite
|
Sign up to set email alerts
|

The neutralizing antibody GNbAC1 abrogates HERV-W envelope protein-mediated oligodendroglial maturation blockade

Abstract: Beyond immune cell modulation, this monoclonal antibody may therefore help to overcome the oligodendroglial differentiation blockade in MS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
52
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 10 publications
6
52
0
2
Order By: Relevance
“…Pre-clinical studies showed that GNbAC1 neutralizes the MSRV-Env target (Rolland et al, 2006;Kremer et al, 2014). GNbAC1 had been studied first in a phase I clinical trial in 33 healthy subjects, showing a good safety as well as a linear pharmacokinetics (Curtin et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Pre-clinical studies showed that GNbAC1 neutralizes the MSRV-Env target (Rolland et al, 2006;Kremer et al, 2014). GNbAC1 had been studied first in a phase I clinical trial in 33 healthy subjects, showing a good safety as well as a linear pharmacokinetics (Curtin et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Yet the precise association between HIV and MS still remains unresolved. For enhanced understanding of the basic mechanisms behind the role of Recent reports have revealed that MS patients treated with GNbAC1 showed signs of improvement, which suggests neuroprotective attributes of GNbAC1, thus supporting its potential as a safe, promising and better long-term treatment option for MS patients [41][42][43].…”
Section: Hiv Connection With Msmentioning
confidence: 99%
“…9 Another effect of MSRV-Env is the blockade of the oligodendrocyte differentiation necessary for the remyelination process, also mediated by an interaction with TLR4 on oligodendrocyte precursor cells (OPCs). 10 Based on the ability of MSRV-Env to activate the innate immune system and given its direct toxicity on OPCs, MSRV-Env is a relevant therapeutic target for MS.…”
mentioning
confidence: 99%